O processo histórico da educação infantil: um olhar reflexivo a partir da realidade de Capivari do Sul - Silva, Maria Cristina Dias de Souza (2010)
This Professional Master s Degree research, titled The historical process of infant education: a reflective view from the reality of Capivari do Sul, aims at describing the child s reality from Middle Age onwards and researching the history of infant education in Brazil along the nineteenth and twentieth century. In order to do so, we laid emphasis on the socio-economical events which were happening in the world and tried to point out where Brazil was in this context, so that we could better comprehend how and why the day care centers and kindergartens arose in Brazil. We sought to dialogue with authors who have been reflecting and discussing about the history of children, infancy, family, education and infant education. We pointed out some considerations about infant education, such as the increase of discussions concerning the theme of infant education that was stronger in the middle of the twentieth century; besides this, we referred to the changes that occurred in the family and the repercussion of it in the relationship with the educational institution. We also found the increase of institutions that provide infant education to children aged 2-6, caused by the fact that the woman start to work outside home. Even in Capivari do Sul, which is a small county, we verified that the cited changes are also part of its social context with greater or lesser intensity. The demands of post-modernity are latent both in the big cities and in the countryside counties.